Conjunctival extranodal marginal zone lymphoma of mucosa-associated lymphoid tissue in the fornix: do not overlook conjunctival lymphomas - Hata M (Dove Medical Press, 2013)
Masayuki Hata,1 Kazuaki Miyamoto,1 Ken Ogino,1 Shinji Sumiyoshi,2 Nagahisa Yoshimura11Department of Ophthalmology and Visual Sciences, 2Department of Diagnostic Pathology, Kyoto University Graduate School of Medicine, Sakyo, Kyoto, JapanBackground: Here we report three cases of conjunctival lymphoma that were initially unnotified or misdiagnosed as other ocular diseases because of the small tumor size, peripheral tumor location (the tumor was hidden in the fornix), and nonspecific symptoms.Methods: Three patients diagnosed with conjunctivitis or nasolacrimal duct obstruction were referred to our clinic because they were unresponsive to standard medical treatments. Routine anterior segment examination did not reveal any lesions, but further careful examination with a strong eyelid draw revealed minimally elevated tumors in the peripheral fornix under the lid. Excisional biopsies were performed.Results: Histopathologic and immunohistologic examinations indicated the presence of extranodal marginal zone lymphoma of mucosa-associated lymphoid tissue (MALT lymphoma). All patients underwent additional radiation therapy. There was no evidence of recurrence in any patient during the follow-up period.Conclusion: Detection of conjunctival lymphoma can be challenging. If no apparent lesion is present and the patient has nonspecific symptoms, the inner surface of the eyelid should be carefully examined. Elaborate eyelid eversion, with eyeball movement, should be performed to avoid misdiagnosing or overlooking peripheral conjunctival lymphomas.Keywords: MALT lymphoma, conjunctival lymphoma, misdiagnosis, fornix